Biomechanical Characteristics of Osteochondral Defects of the Humeral Capitellum. (August 2013) - Mihata, Teruhisa; Quigley, Ryan; Robicheaux, Grant; McGarry, Michelle H.; Neo, Masashi; Lee, Thay Q.
Background: The repetitive, excessive compression forces in the radiocapitellar joint caused by elbow valgus stresses during throwing motions can result in osteochondritis dissecans (OCD) of the humeral capitellum in adolescent athletes. Purpose: To assess the effect of elbow valgus torque on contact pressure in the radiocapitellar joint and that of central and lateral capitellar osteochondral defects on radiocapitellar joint contact pressure, elbow valgus laxity, and ulnar collateral ligament (UCL) strain. Study Design: Controlled laboratory study. Methods: In 8 matched pairs of fresh-frozen cadaveric upper limbs, lateral osteochondral defects of the humeral capitellum (5-, 10-, 15-, and 20-mm diameters) were evaluated in one side, and central defects were evaluated in the contralateral side. Radiocapitellar joint contact pressure, elbow valgus laxity, and UCL strain were all measured with and without 2 N·m of valgus torque at 30°, 60°, and 90° of elbow flexion in neutral forearm rotation. Results: Applying valgus torque increased contact pressure in radiocapitellar joints with intact or damaged capitula. Contact pressure in joints with 15-mm (90° of elbow flexion) and 20-mm (60° and 90° of elbow flexion) lateral capitellar defects was greater than that in joints with intact capitula. Radiocapitellar contact pressure was greater with a 20-mm lateral capitellar defect than in the same-sized central defect at 60° and 90° of elbow flexion. In both central and lateral defect groups, elbow valgus laxity increased as the size of the capitellar defect increased, and UCL strain remained unchanged regardless of the size of the capitellar defect. Conclusion: Elbow valgus torque increases contact pressure in the radiocapitellar joint. Capitellar osteochondral defects increase elbow valgus laxity and contact pressure without increasing UCL strain. When valgus torque is applied, contact pressure in the radiocapitellar joint is greater with a lateral defect than with a central defect. Clinical Relevance: Adolescent baseball players with capitellar OCD should stop throwing, even if the UCL is intact, to prevent exacerbating the osteochondral defect. Lateral capitellar OCD is more severe than central capitellar OCD.